Trust Is Not Enough: Accuracy, Error, Randomness, and Accountability in an Algorithmic Society: Searching for improved algorithmic accountability. - Moss, Emanuel (Communications of the ACM, 2023)
The article discusses the need for accountability from those responsible for search algorithms, including software engineers, corporate officers, institutions, and licensing agencies. Challenges in developing a mechanism for accountability in algorithmic systems are presented, as is the need to address the potential harms caused by algorithmic systems. A significant barrier to accountability includes shifting the blame for errors to external, uncontrollable factors, which the authors refer to as scapegoating.